Islamic boarding school governance and Islamic boarding school education from the perspective of Qur'anic ethics with a case study of Al-Khoziny - Ade Aspandi; Sukron Sukron; Adlan Khoerul Abdi; Ali Mumin Budiman; Sopandi Sopandi (Journal of Mathematics Instruction, Social Research and Opinion, 2026)
Islamic boarding schools (pesantren) serve as important institutions for religious education, character formation, and community development in Indonesia. Alongside their educational mission, pesantren are increasingly required to strengthen governance practices to ensure institutional sustainability, educational quality, and public trust. The collapse of a building within the Al-Khoziny Islamic Boarding School complex attracted public attention and raised broader questions regarding institutional governance, risk management, and educational responsibility in pesantren environments. However, previous studies have primarily examined pesantren from leadership, curriculum, and management perspectives, while limited research has explored governance and educational responsibility through a Qur’anic ethical framework. This study aims to analyze Islamic boarding school governance and Islamic boarding school education from the perspective of Qur’anic ethics using the Al-Khoziny case as an institutional reflection. The research employs a qualitative library-based approach combined with a case-based institutional analysis. Data were collected from Qur’anic verses, hadith literature, classical and contemporary tafsir, scholarly publications on Islamic education, and documented information related to the Al-Khoziny case. Data analysis was conducted through a dialectical hermeneutic process consisting of textual interpretation, ethical abstraction, and institutional contextualization. The findings indicate that the Qur’anic principles of al-‘adl (justice), al-amanah (trustworthiness), and al-ihsan (excellence) provide an integrated ethical foundation for strengthening governance and educational practices in pesantren. The Al-Khoziny case highlights the importance of accountability, transparency, institutional supervision, and continuous improvement as essential dimensions of pesantren management. The analysis further demonstrates that Qur’anic ethical values can guide institutional decision-making while supporting the educational mission of fostering responsibility, integrity, and social awareness among students and stakeholders. This study concludes that effective pesantren governance cannot be separated from ethical values embedded in Islamic teachings. The integration of justice, trustworthiness, and excellence contributes to the development of governance systems that support both educational objectives and institutional resilience. The proposed Qur’anic institutional ethics model offers practical guidance for pesantren leaders in strengthening governance, educational quality, stakeholder participation, and long-term institutional sustainability.